The Queen on the Frontline - Barrera Aravena, Katerín (Nomadías, 2016)
This article attempts to show how the main character of Tengo miedo torero, a ‘queen’, is opposed to two patriarchal systems: on one hand the imperious system and on the other hand the guerrilla system. In this literary work, homosexuality is depicted as coming from aesthetics proper to camp, queer where performance is revealed. We will analyze the way La Loca del Frente uses these three elements to cope with her life in a military and macho/male context, usually kept away from contingence, but dedicated to the guerrilla cause, either guided or blinded by love. This political awareness is what gives to the camp, queer and performance a deep and committed meaning by transforming itself into weapons struggling against the dictator and making him emotional.